Tracing animal genomic evolution with the chromosomal-level assembly of the freshwater sponge Ephydatia muelleri - Nathan J. Kenny (Nature Portfolio, 2020)
Reconstructing the early molecular evolution of animals requires genomic resources for non-bilaterian animals. Here, the authors present the chromosome-level genome of a freshwater sponge together with analyses of its genome architecture, methylation, developmental gene expression, and microbiome.